The Microbiome and Development: A Mother's Perspective - Prince, Amanda L.; Antony, Kathleen M.; Ma, Jun; Aagaard, Kjersti M. (Seminars in Reproductive Medicine, 2014)
Dysbiosis of the microbiome has been associated with type II diabetes mellitus, obesity, inflammatory bowel disorders, and colorectal cancer, and recently, the Human Microbiome Project Consortium has helped to define a healthy microbiome. Now research has begun to investigate how the microbiome is established, and in this article, we will discuss the maternal influences on the establishment of the microbiome. The inoculation of an individual's microbiome is highly dependent on the maternal microbiome, and changes occur in the maternal microbiome during pregnancy that may help to shape the neonatal microbiome. Further, we consider how mode of delivery may shape the developing microbiome of a neonate, and we end by discussing how the microbiome may impact preterm birth and the possibility of bacterial colonization of the placenta. Although the current literature demonstrates that the transformation of the maternal microbiome during pregnancy effects the establishment of the neonatal microbiome, further research is needed to explore how the microbiome shapes our metabolism and developing immune system.
Keywords: microbiome; pregnancy; Human Microbiome Project (HMP) consortium